Insights into the Single Atom and Support Interaction in Electrocatalytic Oxygen Evolution Reaction - Walter C.; Singh A.K.; Sontheimer T.; Indra A.; Menezes P.W. (My University, 2025)
Electrochemical water oxidation with single atom catalysts (SACs) has garnered immense interest because of their high atom utilization, extraordinary activity, and elucidation of the reaction mechanism. In SACs, while the atomic sites offer active centers for substrate binding and reaction intermediates, their interaction with the solid support is crucial for the stabilization and enhancement of catalytic activity. Coordinated elements surrounding the atomic site create a ligand-like environment that influences electrochemical properties. As a result, tuning the coordination environment of SACs allows for modulation of their oxygen evolution reaction (OER) activity. In light of this, the question arises: What is the role of the support in stabilizing single atoms (SAs) and controlling their electrochemical activity during water oxidation? This review addresses this question using recent examples. Spectroscopic characterizations and density functional theory (DFT) calculations provide a direct answer: In SACs, the atomic centers exhibit strong interactions with the support via neighboring atoms, influencing OER activity. © 2024 The Authors. ChemElectroChem published by Wiley-VCH GmbH.